IL-35 Regulates the Function of Immune Cells in Tumor Microenvironment - Liu, Kewei; Huang, Ai; Nie, Jun; Tan, Jun; Xing, Shijie; Qu, Yue; Jiang, Ke (Frontiers in Immunology, 2021)
IInterleukin-35 (IL-35) is a heterodimeric cytokine composed of Epstein-Barr virus-induced gene 3 (EBI3) and IL-12p35 that has recently been shown to play diverse and important roles in the tumor microenvironment (TME). Owing to its immunosuppressive activity and ability to promote tumor growth and progression, IL-35 is widely recognized as a key mediator of TME status. Immune cells are key mediators of diverse tumor-related phenotypes, and immunosuppressive cytokines such as IL-35 can promote tumor growth and metastasis in TME. These influences should be considered together. Since tumor immunotherapy based on immune checkpoint blockade remains ineffective in many patients due to tumoral resistance, a new target or efficacy enhancing factor is urgently needed. Suppressing IL-35 production and activity has been demonstrated as an effective factor that inhibits tumor cells viability, and further investigation of this cytokine is warranted. However, the mechanistic basis for IL-35-mediated regulation of immune cells in the TME remains to be fully clarified. In the present review, we explore the roles of IL-35 in regulating immune cells within the TME. In addition, we highlight IL-35 as a specific immunological target and discuss its possible relevance in the context of immunotherapy. Lastly, we sought to summarize potential future research directions that may guide the advancement of current understanding regarding the role of this important cytokine as a regulator of oncogenesis.